(untitled) (Archives of Criminology, 2008)
The article is a study of the factors influencing the change in how the institution of conditional early release (from serving the remainder of a prison sentence) is applied for juveniles. The issue presented in the text pertains to conclusions from penitentiary research conducted by the author in the penal facility for juveniles in Wloclawek on convicts who applied for conditional release in the years 1996, 1999, and 2002. The aim of the analysis undertaken by Paulina Wiktorska is to assess the effectiveness of the application of the institution of conditional early release by this penitentiary court. The study concerns two cases of convicts – those released conditionally in a given year without applying for this institution and juvenile offenders who had previously applied for conditional early release and had the court rule against their application. In conclusion, the author cites the reasons for refusing to grant conditional release, such as general prevention goals, a premature end of the sentence, a disproportion between the sentence served and the sentence imposed, a failure to achieve the retributive function of the punishment, or citing grounds that do not comply with the requirements of the Penal Code. Wiktorska draws the readers’ attention to the necessity of focussing more on the conditions on which conditional early release is granted, rather than on tightening the policy of granting it. The primary goal of using this institution should be a preparation for freedom and not only a remission of part of a sentence.